Instructional Strategies for Training Competent Technical Teachers and Instructors in Uganda - Mukasa, J. Ddungu-Kafuluma; Simiyu, John; Wanami, Simon (African Journal of Education,Science and Technology (AJEST), 2020)
Competent Technical and Vocational Education Teachers are critical in the training of a skilled workforce, which is globally competitive and can effectively contribute to sustainable economic growth and development. For technical teachers and instructors to be globally competitive, their training has to be based on effective instruction. From a qualitative perspective, this paper explores expert views on what is needed to have well-trained and effective technical teachers and instructors in Uganda. Information was collected from 36 respondents who included, senior technical education trainers (n=15), Managers of Technical and Vocational Education and Training (TVET) institutions (n=6), Ministry of Education and Sports officers from Teacher Instructor Education and Training department (n=5), examiners of Technical and Vocational Education and Training trainees from Uganda Business Technical Examinations Board (n=3) and industrialists (n=7). Data was collected using key informant interviews and documentary review and analyzed using Pragmatic Content Analysis. The findings show that strategies that promoted experiential and constructive learning and teaching were more appropriate for the training of effective technical teachers and instructors. These methods were appropriate because they combined scientifically grounded knowledge base, skills and values, needed by technical education instructors with tacit knowledge and competence. These instructional strategies also promoted the ability of trainees to analyze learning needs of students, design and manage learning. The strategies further enhanced technical teachers’ and instructors’ competence in modelling students who can explore, manipulate, experiment, question, and search for answers by themselves. The results provide important lessons to improve the training of technical teachers and instructors in Uganda. Therefore, experiential and constructive training methods should be infused into Technical and Vocational Education teacher and instructor training in Uganda to improve the quality of Technical and Vocational Education teachers and instructors. Using this mode of training will reduce inefficiencies in the current practices that are largely based on theoretical orientations.